Ethnodemographic characterization of stroke incidence and burden of disease in hospital discharge records in Ecuador - Carrington, Sarah J.; Romero-Alvarez, Daniel; Coral-Almeida, Marco; Vela, Andrea; Henríquez-Trujillo, Aquiles Rodrigo; Mascialino, Guido (Frontiers in Neurology, 2023)
Stroke is the second most common cause of death and disability-adjusted life years (DALYs) globally. However, the incidence and impact of stroke by ethnicity and gender is frequently distinct. This is particularly the case in Ecuador where geographical and economic marginalization are often correlated with ethnic marginalization and the extent to which females share the same opportunities as their male counterparts. This paper calculates the differential impacts in terms of stroke diagnosis and burden of disease by ethnicity and gender, using hospital discharge records over the years 2015 – 2020. The results show that while the incidence rate of stoke in males (64.96 per 100,000 persons-year) is higher than that for females on average (57.84 per 100,000 persons-year), males accounted for 52.41% of all ACV cases and 53% of all surviving cases. Thus, females had an overall significantly higher death rate of 31.6% when compared to males with a death rate of 28.7% (p<0.0001). Case fatality rates also differed significantly by ethnicity: The highest fatality rate corresponded to Montubio ethnic group (87.65%), second were Afrodescendants (67.21%). The estimated burden of disease of ACV in Ecuador (2015-2020) varied from 1.468 to 2.991 DALY per 1000 population on average.